Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To convert the given quadratic function from standard form \( f(x) = x^2 - 2x - 6 \) to vertex form, we'll use the method of completing the square. Here’s a detailed, step-by-step solution:
1. Rewrite the function as \( ax^2 + bx + c \):
[tex]\[ f(x) = x^2 - 2x - 6 \][/tex]
Here, \(a = 1\), \(b = -2\), and \(c = -6\).
2. Isolate the quadratic and linear terms:
[tex]\[ f(x) = (x^2 - 2x) - 6 \][/tex]
3. Complete the square:
To complete the square, first find the value that completes the square for the quadratic expression inside the parentheses. The term needed to complete the square is \(\left(\frac{b}{2}\right)^2\).
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
Add and subtract this value inside the parentheses:
[tex]\[ f(x) = (x^2 - 2x + 1 - 1) - 6 \][/tex]
Combine the complete square and the remaining terms:
[tex]\[ f(x) = [(x - 1)^2 - 1] - 6 \][/tex]
4. Simplify the expression:
Combine the constants outside the square:
[tex]\[ f(x) = (x - 1)^2 - 1 - 6 \][/tex]
[tex]\[ f(x) = (x - 1)^2 - 7 \][/tex]
Therefore, the function in vertex form is:
[tex]\[ f(x) = (x - 1)^2 - 7 \][/tex]
So, the correct choice is:
- \( f(x) = (x - 1)^2 - 7 \)
This corresponds to the given result that validates our solution.
1. Rewrite the function as \( ax^2 + bx + c \):
[tex]\[ f(x) = x^2 - 2x - 6 \][/tex]
Here, \(a = 1\), \(b = -2\), and \(c = -6\).
2. Isolate the quadratic and linear terms:
[tex]\[ f(x) = (x^2 - 2x) - 6 \][/tex]
3. Complete the square:
To complete the square, first find the value that completes the square for the quadratic expression inside the parentheses. The term needed to complete the square is \(\left(\frac{b}{2}\right)^2\).
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
Add and subtract this value inside the parentheses:
[tex]\[ f(x) = (x^2 - 2x + 1 - 1) - 6 \][/tex]
Combine the complete square and the remaining terms:
[tex]\[ f(x) = [(x - 1)^2 - 1] - 6 \][/tex]
4. Simplify the expression:
Combine the constants outside the square:
[tex]\[ f(x) = (x - 1)^2 - 1 - 6 \][/tex]
[tex]\[ f(x) = (x - 1)^2 - 7 \][/tex]
Therefore, the function in vertex form is:
[tex]\[ f(x) = (x - 1)^2 - 7 \][/tex]
So, the correct choice is:
- \( f(x) = (x - 1)^2 - 7 \)
This corresponds to the given result that validates our solution.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.